2
$\begingroup$

I apologize if this is a super easy question, but there is something fishy about my proof.

I was to show:

$$(p,q) \sim (m,n) \wedge (m,n) \sim (a,b) \implies (p,q) \sim (a,b) $$

under the equivalences relation of rational numbers (i.e. $(a,b) \sim (c,d) \equiv a,b,c,d \in \mathbb{Z}, ad = bc \wedge b,d \neq 0$).

So what I have is that I know that the LHS ($(p,q) \sim (m,n) \wedge (m,n) \sim (a,b)$) of what I want to show means I know by assumption that the following is true:

  1. $pn=mq$, $q,n \neq 0$
  2. $mb=an$, $n,b \neq 0$ and we want to show:
  3. $pb = aq$, $n,b \neq 0$

Its pretty obvious to show $n,b \neq 0$ but I feel I am doing something wrong when trying to apply the cancellation law.

I have $pn=mq$ is true and multiply that by $a$ and $b$ to get:

$$anpb = mbaq$$

since we know $mb=an$ we can use the cancellation law to get:

$$(an)pb = (mb)aq \rightarrow pb = aq$$

Just as I required. However, I don't think this proof is correct, because no where in the assumption did we ever say that $a \neq 0$, so $a$ might not have a multiplicative inverse in the group of integers. Is this proof correct or do I have to handle the case where the "numerators" might be zero separately?

$\endgroup$
2
  • 6
    $\begingroup$ If $a=0$ then $p=0$ since by assumption $b \neq 0$ and therefore $m=0$ since by assumption $q \neq 0$ and the result holds. (In the same way if you take $m=0$ yo can deduce that $a=0$) $\endgroup$ Jun 7, 2015 at 18:49
  • 1
    $\begingroup$ Handling the zero case separately is the safe thing to do, as it often is in algebra. $\endgroup$
    – Arthur
    Jun 7, 2015 at 18:50

1 Answer 1

4
$\begingroup$

We have $(p,q)\sim(m,n)$ and $(m,n)\sim(a,b)$ and we know that integer multiplication is commutative. Now we have the following using $pn=mq$ and $mb=an$:

$$pbn=pnb=mqb=qmb=qan=aqn$$

Hence we may cancel $n\neq0$ from the right hand side and obtain $pb=aq$. In particular we have shown that $(p,q)\sim(a,b)$ and so the relation is transitive as desired.

$\endgroup$
1
  • $\begingroup$ Note that there is no need to treat the zero-case separately in this instance. $\endgroup$
    – User12345
    Jun 7, 2015 at 23:35

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.